2018
DOI: 10.21276/apalm.1740
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Gallbladder Lesions

Abstract: Background: Gallbladder is one of the most frequently surgically resected organs which stores and concentrates the bile and is involved by both non neoplastic as well as neoplastic diseases. Chronic calculous cholecystitis is the most common benign lesion of gallbladder and pain abdomen is the commonest clinical presentation. Both non neoplastic and neoplastic lesions have similar clinical presentation and overlapping radiological findings. Methods:Total 550 cholecystectomy specimens were received in pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Comparison of incidence of gallbladder carcinoma in the present study with other studies: Incidence of carcinoma gallbladder found in the present study was 1.89% (6 cases), which correlated very well to the incidence found in the study conducted by Murmu S et al [10] (2 cases, 1.88%), Kumar H et al [11] (North Indian data-8 cases, 2%, South Indian data-5 cases, 1.25%) and the study by Kumari G et al [12] (7 cases, 1.27%). A lower incidence was observed in studies done by Beena D et al [13] (1 case, 0.5%), Mondal B et al [14] (5 cases, 0.6%), Sharma I et al [15] (3 cases, 0.86%) and H Mohan et al [16] (12 cases, 1.09%).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Comparison of incidence of gallbladder carcinoma in the present study with other studies: Incidence of carcinoma gallbladder found in the present study was 1.89% (6 cases), which correlated very well to the incidence found in the study conducted by Murmu S et al [10] (2 cases, 1.88%), Kumar H et al [11] (North Indian data-8 cases, 2%, South Indian data-5 cases, 1.25%) and the study by Kumari G et al [12] (7 cases, 1.27%). A lower incidence was observed in studies done by Beena D et al [13] (1 case, 0.5%), Mondal B et al [14] (5 cases, 0.6%), Sharma I et al [15] (3 cases, 0.86%) and H Mohan et al [16] (12 cases, 1.09%).…”
Section: Discussionsupporting
confidence: 92%
“…These results were comparable to the study done by Levy DA et al [17] in which 68% cases were grey white irregular mass lesions and 60% of the tumour originate in fundus of the gallbladder. Also comparable to the study done by Kumari G et al [12] where 90% of the cases were grey white irregular mass lesions.…”
Section: Comparison Of Characteristics Of Growth In Gallbladder Carcisupporting
confidence: 90%
See 2 more Smart Citations
“…1 Gallbladder lesions are very common in fatty, fertile, females of around forty age group. 2 In India and in western countries, the incidence of cholelithiasis is increasing due to change in lifestyle, food habits and consumption of alcohol. 2 The gallstone disease prevalence is 6-12% in India and 10-15% in Western population.…”
Section: Introductionmentioning
confidence: 99%